Treatment of acute appendicitis with one-port transumbilical laparoscopic-assisted appendectomy: A six-year, single-centre experience - Guanà R; Gesmundo R; Maiullari E; Bianco E; Bucci V; Ferrero L; Canavese F (Wolters Kluwer Medknow Publications, 2010)
Background: Laparoscopic appendectomy is a feasible and safe alternative to open appendectomy for uncomplicated appendicitis. In the past decade several laparoscopic procedures have been described using one or more ports. We report our experience in treating acute appendicitis with one-port transumbilical laparoscopic-assisted appendectomy (TULAA). Patients and Methods: We performed 231 TULAA on patients in the period from November 2001 to September 2007. We introduced an 11 mm Hasson′s port using open technique; an operative channel with 10 mm telescope and an atraumatic grasper were used. After intra-abdominal laparoscopic dissection, the appendix was exteriorised through the umbilical access. The appendectomy was performed outside the abdomen as in the open procedure; the operation was completed using only one port in 227 patients (98%), two and three ports in two patients (1%) while conversion to open surgery was needed in two patients (1%). Results: The average operating time was 38 minutes and the median time to discharge was three days. Four (1, 7%) early postoperative complications (two suppuration of the umbilical wound) with no major complications were observed. Conclusions: Our results demonstrate that TULAA, which combines the advantages of both open and laparoscopic procedures, is a valid alternative form of treating uncomplicated appendicitis. If appendectomy cannot be completed with only one port, insertion of one or more ports may be necessary to safely conclude the procedure.